Evaluation of Drug Interaction Potential and Influencing Factors in Patients with Type 2 Diabetes Mellitus with Comorbid Hypertension - Qoyimatul Adilah; Yolanda Safitri; Shinta Dewi Permata Sari (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2026)
Background: Diabetes mellitus type 2 (DMT2) patients with hypertension are often prescribed multiple medications simultaneously, increasing the risk of drug interactions, which potentially cause adverse effects and impact patient outcomes. Consequently, potential drug interactions should be identified to improve drug safety. Purposes: This study aims to analyze potential drug interactions and investigate the associated factors in DMT2 patients with hypertension and other comorbidities. Methods: This observational, analytical study with a cross-sectional design collected data from the medical records of 107 patients at Jakarta Islamic Hospital Pondok Kopi from October 2022 to October 2023. Potential drug interactions were identified using Lexicomp software, and statistical analysis was conducted using the chi-squared and Fisher’s exact tests. Results: A total of 310 potential drug interactions were identified in 107 prescriptions (95.3%), with the most frequent drug combination being glimepiride-metformin (4.9%). The severity of potential drug interactions was classified as moderate (78.8%), minor (13.8%), and major (2.8%), and the potential drug interaction mechanisms were dominated by pharmacodynamic mechanisms (81.5%). The number of medications was found to be the only factor that significantly influenced potential drug interactions (p<.05). Polypharmacy increased the risk of potential drug interactions 6.7 times over non-polypharmacy prescriptions. The most prevalent drug interaction, between glimepiride and metformin, was classified as moderately severe, with pharmacodynamics being the primary mechanism. Conclusion: This study concluded that the number of drugs was the sole factor influencing the occurrence of potential drug interactions in this population.